2001
DOI: 10.1021/jp0040749
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Electrical Conductivity and Surface Spectroscopic Studies of Indium−Tin Oxide

Abstract: Optically transparent indium-tin oxide (ITO) is a "universal" electrode for various optoelectronic devices such as organic light emitting diodes (OLEDs). It is known that the performance of OLEDs improves significantly by exposing the ITO surface to an oxygen plasma. This study employs conducting atomic force microscopy (C-AFM) for unique nanometer-scale mapping of the local current density of a vapor-deposited ITO film. The local conductance is shown to increase by orders of magnitude and becomes more uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 38 publications
6
91
0
Order By: Relevance
“…Several researchers have proposed that the main conduction mechanism of ITO films deposited at low-substrate temperature is due to the creation of oxygen vacancies, which donate two electrons for each vacancy [23][24][25]. Some of the researchers used plasma surface treatment [26][27][28] such as oxygen plasma treatment in order to improve ITO conductivity. The plasma surface treatment identified different factors which affected surface electrical properties: (1) removal of surface carbonaceous contamination, (2) changes in the In/Sn ratio indicative of the Sn dopant concentration, (3) changes in the concentration of oxygen vacancies, and (4) producing oxidation of Sn-OH surface groups to Sn-O * species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have proposed that the main conduction mechanism of ITO films deposited at low-substrate temperature is due to the creation of oxygen vacancies, which donate two electrons for each vacancy [23][24][25]. Some of the researchers used plasma surface treatment [26][27][28] such as oxygen plasma treatment in order to improve ITO conductivity. The plasma surface treatment identified different factors which affected surface electrical properties: (1) removal of surface carbonaceous contamination, (2) changes in the In/Sn ratio indicative of the Sn dopant concentration, (3) changes in the concentration of oxygen vacancies, and (4) producing oxidation of Sn-OH surface groups to Sn-O * species.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma surface treatment identified different factors which affected surface electrical properties: (1) removal of surface carbonaceous contamination, (2) changes in the In/Sn ratio indicative of the Sn dopant concentration, (3) changes in the concentration of oxygen vacancies, and (4) producing oxidation of Sn-OH surface groups to Sn-O * species. Liau et al [28] proved that the oxidation of Sn-OH surface groups to Sn-O * species is the most probable factor that enhances ITO conductivity. Thus, presence of Sn-OH surface groups on the surface of our ITO films can be accounted as another reason for the obtained high resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies of neat electrode materials have demonstrated a great deal of heterogeneity in their electronic characteristics. Both Armstrong and coworkers [24] and Liau et al [25] applied c-AFM to study the effects of different surface treatments on the electrical homogeneity of tin-doped indium oxide (ITO) surfaces. Both groups found that the surface resistance of ITO varied considerably on $50-200 nm length scales, and Armstrong and coworkers demonstrated that while common treatments, such as like oxygen-plasma cleaning, improved the surface conductivity and uniformity, the largest values of surface conductance were obtained after a brief etch in haloacids (Fig.…”
Section: Variations In Local Charge Transport Probed With Conductive Afmmentioning
confidence: 99%
“…In particular, when atomic-force microscopy is used in combination with a conductive tip (C-AFM), it can provide functional information about samples containing conducting and insulating regions [17][18][19][20][21]. Topographic and current images can be obtained simultaneously for a variety of systems, thus providing information about the distribution of conducting islands surrounded by insulating areas and relationships between structural features and electrical properties on the nanometer scale that are impossible to obtain by EC-STM [22,23]. To determine local resistivities of a metal, a potential difference is applied between a conducting tip (Pt, Pt/Ir, Ti, doped diamond) that is in mechanical contact with the sample surface (Fig.…”
Section: Introductionmentioning
confidence: 99%